E-COMMERCE PADA CV. ANUGERAH PRATAMA PRESS: CodeIgniter;CV.Anugerah Pratama Press Printing Data;E-Commerce;Data Processing;Wampserver. - Windy Adriana; Suharman, Dede (LP2M Universitas Nurdin Hamzah, 2021)
CV. Anugerah Pratama Pressis one of the businesses that is engaged in printing. Information about the types of printed products is obtained by consumers by coming directly to the places it is still less effective. Therefore, an E-Commerce information system is needed so that the products sold by CV Printing. Anugerah Pratama Pressis better known to the public. E-Commerce was developed using software, namely Sublime Text 3, Wampserver, PHP programming language, and MySQL as the database. The purpose of designing an E-Commerce website is to understand the sales system and online sales strategy to increase profits and ease the ordering process.